The Effect of Thyroid Hormone Replacement on the Metabolic Control and Insulin Resistance in Patients with Subclinical Hypothyroidism - Roohigilani, Kobra; Ebadi, Seyed Alireza; Hajighasemi, Mohsen; Shahrzad, Mohammad Karim; Pishgahi, Mehdi (Archives of Men’s Health, 2021)
Introduction: Studying the treatment effect of subclinical hypothyroidism in decreasing metabolic syndrome risk factors and cardiovascular diseases is necessary and can be helpful to control future disorders. In spite of various studies, the relationship between subclinical hypothyroidism and cardiovascular diseases remain controversial. Studies which consider the effects of subclinical hypothyroidism treatment on metabolic control and insulin resistance have not been done in the Islamic Republic of Iran yet. Materials and methods: In this interventional study, 153 patients with subclinical hypothyroidism (thyroid stimulation hormone (TSH) >5, normal T3 and T4 at least 2 times) were selected from Labbafinejad endocrine clinic. Laboratory tests were performed at 8 a.m. after 12-14 hours fasting. Patients were then treated with levothyroxine (25-50 µg daily). To adjust the dose, thyroid function tests (TFT) were checked every 2 months for 6 months. Collected data was used for analysis by spss18 software. Results: After 6 months treatment of subclinical hypothyroidism mean values improved in factors such as insulin resistance profile (fasting blood sugar (FBS), 2 hours post prandial (2hPP), fasting insulin and homeostasis model assessment estimated insulin resistance (HOMA-IR index), lipid profile (total cholesterol, low density lipoprotein (LDL) and high density lipoprotein (HDL), decreased c-reactive protein (CRP) and weight (all had P value<0.05). Treatment did not have significant effect on triglycerides (TG), waist circumference, body mass index (BMI), uric acid ad systolic/diastolic blood pressure (p values>0.05). But the number of cases with high systolic/diastolic blood pressure decreased significantly after 6 months treatment (P values=0.007 and 0.01). Conclusion: Subclinical hypothyroidism treatment is suggested according to mentioned effects, especially in cases with insulin resistance, lipid profile disturbance, obesity, and high blood pressure.